(untitled) (Foro de Educacion, 2019)
Language socialization research in bilingual and multilingual settings, particularly across EFL (English as a Foreign Language) and ESL (English as a Second Language) contexts, has addressed the processes by which novices are «apprenticed» or mentored into the linguistic and nonlinguistic ideologies, values, practices, and stances (affective, epistemic, and other) of sociocultural groups to ultimately become «competent members» of these learning communities. However, one of the unexplored bilingual education contexts from a language socialization perspective refers to «Content and Language Integrated Learning» or CLIL, defined as «inclusive of a wide range of educational practices provided that these practices are conducted through the medium of an additional language and both language and the subject have a joint role». Taking these premises as a point of departure, this article discusses the language socialization processes CLIL teachers undergo to become competent members of the bilingual school communities (BSC) that have proliferated extensively in Castilla-La Mancha (CLM), Spain, in the last decade. Drawing on ethnographic data collected in four different bilingual state-funded and state-funded private schools in this region, the article analyzes the case of San Marcos’ teachers’ narratives of becoming and doing CLIL as «meta-agentive» discursive sites that display the ideologies and practices of professional personhood at stake in CLIL programs. The article further advances the latest ethnographic CLIL agenda interested in revealing the social processes involved in the organization of exclusionary practices in the era of the «bilingual» craze and pressure across different Spanish autonomous communities